PENGEMBANGAN MEDIA PEMBELAJARAN KIMIA BERBASIS GUIDED DISCOVERY PADA MATERI LARUTAN PENYANGGA - Salastri Rohiat; Sura Menda Ginting; Ica Nur Azizah (University of Bengkulu, 2022)
This study aims to determine the level of feasibility and student response to guided discovery-based chemistry learning media that was developed. This type of research is research and development with the ADDIE model. The trial was conducted on a small scale with 30 students of class XII MIPA 1 SMAN 4 Bengkulu City. The research data were obtained from material validation questionnaires, media validation questionnaires and student response questionnaires. From the results of the study, it was found that the feasibility level of chemistry learning media in the material aspect was 89.77% with a very valid category while in the media aspect it was 92.85% with a very valid category. The results of student responses to chemistry learning media obtained a percentage of 92.15% with a very interesting category. These results indicate that the guided discovery-based chemistry learning media on the buffer solution material produced in this study is very feasible to be used in the learning process